Early appearance and spread of fast ripples in the hippocampus in a model of cortical traumatic brain injury - Ortiz, Franco; Zapfe, W. P. Karel; Draguhn, Andreas; Gutiérrez, Rafael (The journal of neuroscience, 2018)
Fast ripples (FRs; activity of >250 Hz) have been considered as a biomarker of epileptic activity in the hippocampus and entorhinal cortex; it is thought that they signal the focus of seizure generation. Similar high-frequency network activity has been produced in vitro by changing extracellular medium composition, by using pro-epileptic substances, or by electrical stimulation. Here we study the propagation of these events between different subregions of the male rat hippocampus in a recently introduced experimental model of FRs in entorhinal cortex-hippocampal slices in vitro. By using a matrix of 4096 microelectrodes, the sites of initiation, propagation pathways, and spatiotemporal characteristics of activity patterns could be studied with unprecedented high resolution. To this end, we developed an analytic tool based on bidimensional current source density estimation, which delimits sinks and sources with a high precision and evaluates their trajectories using the concept of center of mass. With this methodology, we found that FRs can arise almost simultaneously at noncontiguous sites in the CA3-to-CA1 direction, underlying the spatial heterogeneity of epileptogenic foci, while continuous somatodendritic waves of activity develop. An unexpected, yet important propagation route is the propagation of activity from CA3 into the hilus and dentate gyrus. This pathway may cause reverberating activation of both regions, supporting sustained pathological network events and altered information processing in hippocampal networks. - SIGNIFICANCE STATEMENT Fast ripples (FRs) have been considered as a biomarker of epileptic activity and may signal the focus of seizure generation. In a model of traumatic brain injury in the rat, FRs appear in the hippocampus within a couple of hours after an extrahippocampal, cortical lesion. We analyzed the origin and dynamics of the FRs in the hippocampus using massive electrophysiological recordings, allowing an unprecedented high spatiotemporal resolution. We show that FRs originate in distinct and noncontiguous locations within the CA3 region and uncover, with high precision, the extent and dynamics of their current density. This activity propagates toward CA1 but also backpropagates to the hilus and the dentate gyrus, suggesting activation of defined microcircuits that can sustain recurrent excitation.
Gesehen am 12.03.2020